Responsible innovation in France: A proxy allowing agents of the political and economic fields to interact - Bedreddine, Samir (NOvation — Critical Studies of Innovation, 2022)
This article examines the issue of responsible innovation in France. To describe its underlying mechanisms and logics, we retrace the advent of innovation in public policy and its reception in French firms, showing how responsible innovation has become the cornerstone of public-private interactions. The legal and administrative context of innovation in France, on the one hand, the emerging departments and managers of innovation in the large groups, on the other hand, participate in producing spaces where agents of the political and economic fields converge. Such situated interactions hinge on shared world views, values and tools. Innovation managers, executive directors of large firms, some French politicians and public servants seize upon responsible innovation and create areas regulated by specific norms and values. In these shared spaces, responsible innovation is the star object, the proxy for exchanges between the economic and the political fields.